Avaliação bromatológica de salsichas e adequação da rotulagem à legislação vigente - Ana Carolina Santana de Sousa (2012)
The package label is one of the main links between producer and consumer. For the consumer to make his choice of the most appropriate way to get healthier options, it is important that he be able to understand the information expressed on the labels and that these data be reliable. In this work, the information contained on the labels regarding the nutritional properties of a portion of sausage was verified. The choiceof weiner as an object of analysis was based on the statement that there is currently a high consumption of processed products such as wieners in Brazil. This situation has resulted in a considerable increase in the intake of fat and sodium by the Brazilian population. Excessive intake of these substances has increased the incidence of chronic diseases. Indeed, that has been the focus of attention for the Public Health organs and for many consumers. Chemical analyses were performed to determine the energy value and the amount of each nutrient present in a portion of wieners. It was verified that the label was in accordance with the law, and the results were compared with data expressed on the labels of the weiner samples analyzed. In the process, several mistakes, especially in relation to the amounts of carbohydrates, saturated fats, trans fats and dietary fiber were encountered. All the labels had errors and were not in accordance with current legislation.